2015
DOI: 10.31387/oscm0230161
|View full text |Cite
|
Sign up to set email alerts
|

Learning on Lean Production: A Review of Opinion and Research within Environmental Constraints

Abstract: Despite of its type, location or principal market base, today the manufacturing enterprises are bound to adopt sustainable practices like lean principles, integration of processes and inter-organizational collaborations to meet their corporate goals. The majority of studies usually discuss either a system or a subcomponent of the production systems and manufacturing strategies in literature w.r.t. lean production; but the rational (what, why, how) behind each production activity seems to be missing. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 77 publications
2
17
0
Order By: Relevance
“…Therefore, the case study shows that SW and line balancing can have a positive impact for many SMEs in the manufacturing sector. Further, the present findings are consistent with those reported by Mor et al [19], Rahul and Kaler [45], More et al [21], Bhardwaj et al [46], Mor et al [47], and Garg et al [48], where simple techniques have been implemented among SMEs to promote greater production and efficiency. As a practical value, these results, as well as the method and techniques applied, can be used as an improvement reference by SMEs in massive production processes with multiple operators.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the case study shows that SW and line balancing can have a positive impact for many SMEs in the manufacturing sector. Further, the present findings are consistent with those reported by Mor et al [19], Rahul and Kaler [45], More et al [21], Bhardwaj et al [46], Mor et al [47], and Garg et al [48], where simple techniques have been implemented among SMEs to promote greater production and efficiency. As a practical value, these results, as well as the method and techniques applied, can be used as an improvement reference by SMEs in massive production processes with multiple operators.…”
Section: Discussionsupporting
confidence: 92%
“…SW is probably the most known method for performing a specific job, which in turn makes it the safest and most efficient method for complying with timely, orderly, and quality deliveries [20]. SW is the set of specific directions that are needed to manufacture a product in the most efficient way, which allows defining the best methods and sequenced tasks for each process and operator, therefore, reducing wastes [19,21,22]. SW defines how each task or job must be performed by each operator in the production system, hence, preventing employees from executing random tasks [19,23] that can adversely affect lifecycle times.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Kern et al (2012) identified that the traditional risk management process (identification, assessment, mitigation) is also sufficient in the SC context. In addition to the risk management approach, for example Mor et al (2016), identifies that in the lean production, by establishing clear environmental goals and rules for acting accordingly, can improve the employee morale and compliance with environmental regulation.…”
Section: Sustainability Performancesmentioning
confidence: 99%
“…The optimal effectiveness is required in the dairy sector to achieve better product quality and food safety [4,5]. Food producers, as well as processors, need to focus on the effective marketing strategies to target the rural market [6][7][8]. An analytic hierarchy process (AHP) approach allows the top management to measure the level of uniformity in finding the decision problems [9].…”
Section: Introductionmentioning
confidence: 99%